Conceptual design of spatial arch footbridges supporting curved decks. (October 2021) - Todisco, Leonardo; Corres, Hugo; Pérez, Alejandro; Addante, Angela; Cañada, Javier
Abstract: Spatial arch footbridges represent an innovative answer to demands on functionality, structural optimization and aesthetics for curved decks, popular in urban contexts. This paper presents a methodology, and its implementation as a tool in a parametric design environment, for the fast determination of the antifunicular shape of spatial arch bridges supporting a curved deck of an arbitrary geometry. Profiting from the interactive design space exploration capacities of the tool, a large parametric analysis is performed. Specifically, the performance of these structural systems, evaluated in terms of internal forces in the structure, is investigated iterating through the domain of relevant design variables: the relative transversal position between arch and deck and the arrangement of hangers. On this basis, this study identifies the influence of some of the parameters governing the behaviour of spatial arch footbridges with the goal of providing guidance on the most appropriate decisions during the conceptual design stage of such structures.